Norvegų kalbos pristatomoji konstrukcija ir jos atitikmenys lietuvių kalboje - Griškevičienė, Aurelija (Kalbotyra, 2004)
The aim of this article is to give an analysis of Norwegian presentative constructions and their equivalents in Lithuanian from the point of view of the Functional Sentence Perspective principle. The material for this study was collected from Lithuanian-Norwegian and Norwegian-Lithuanian fiction translations.The analysis confirmed the assumption that the same function which in Norwegian is fulfilled by presentative constructions, is fulfilled in Lithuanian by word order. The rhematic subject in Lithuanian is usually transferred to the end of sentence. This particular function can be given additional prominence using lexical means.